Endophytic Fungi: From Symbiosis to Secondary Metabolite Communications or Vice Versa? - Alam, Beena; Lǐ, Jùnwén; Gě, Qún; Khan, Mueen Alam; Gōng, Jǔwǔ; Mehmood, Shahid; Yuán, Yǒulù; Gǒng, Wànkuí (Frontiers in Plant Science, 2021)
Endophytic fungi (EF) are a group of fascinating host-associated fungal communities that colonize the intercellular or intracellular spaces of host tissues, providing beneficial effects to their hosts while gaining advantages. In recent decades, accumulated research on endophytic fungi has revealed their biodiversity, wide-ranging ecological distribution, and multidimensional interactions with host plants and other microbiomes in the symbiotic continuum. In this review, we highlight the role of secondary metabolites (SMs) as effectors in these multidimensional interactions, and the biosynthesis of SMs in symbiosis via complex gene expression regulation mechanisms in the symbiotic continuum and via the mimicry or alteration of phytochemical production in host plants. Alternative biological applications of SMs in modern medicine, agriculture, and industry and their major classes are also discussed. This review recapitulates an introduction to the research background, progress, and prospects of endophytic biology, and discusses problems and substantive challenges that need further study.